Analysis of Rice Farming Competitiveness in Bojonegoro Regency - Ningsih, Winnarti; Laily, Dona Wahyuning; Setiawan, Risqi Firdaus (Kadiri University - Faculty of Agriculture, 2024)
Rice plants are one of the leading commodities in Bojonegoro Regency and become a rice producing area in East Java. This observe objectives to determine the competitiveness of rice farming in Bojonegoro Regency. The willpower of the sample region of the district in Bojonegoro Regency is done deliberately through choosing the sample area of the district that has the most important amount of rice production in Bojonegoro Regency. This study used more than one stage of sampling called multistage random sampling. The Data used are primary data and secondary data. The records evaluation used is the policy analysis Matrix (PAM) version. The results showed that rice farming in Bojonegoro is feasible because it has competitive advantages and comparative advantages. This is evidenced by the average value of PCR and DRCR is worth less than 1. PCR value of 0.67 while the DRCR value of 0.58. Thus, it can be concluded that rice farming in Bojonegoro Regency shows excellent performance, both in terms of competitiveness in the market and the efficiency of domestic resource use. This shows that Bojonegoro Regency has positive indicators for the sustainability and development potential of the sector in the future. Therefore, government and farmers must maintain and improve the competitiveness of rice farming in order to obtain maximum profits.